Evaluation Report on Pochampad Irrigation Project (1980-82) - Planning Commission (Planning Commission, 1983)
The Programme Evaluation Organisation of the Planning Commission conducted at the instance of the Ministry of Finance an evaluation study of the Pochampad Irrigation Project in Andhra Pradesh which is one of the externally aided Irrigation Projects in the country. The Agreement with International Development Association (IDA) (an affiliate of the World Bank) was signed by the Government of India in August, 197l. The cost of the various works was estimated at Rs.55.33 crores. The IDA had agreed to provide financial assistance of the order of P.s.29.3 crores. 2, The objectives of the evaluation study were as follows: (i) To study the financial aid available from International Development Association (IDA), terms of agreement, award of contracts including organisation and management aspects.
Programme Evaluation Organisation, Planning Commission, Government of India, New Delhi